The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1093/mmy/myw100
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and antifungal susceptibility study on trichosporonemia and emergence ofTrichosporon mycotoxinivoransas a bloodstream pathogen

Abstract: A total of 21 Trichosporon spp. isolates from blood over a period of 5 years (January 2009 to December 2013) were included in the study. The most common underlying diseases found were pancreatitis (33.3%) and cancer (33.3%). Trichosporon asahii (80.9%) was the commonest species followed by Trichosporon mycotoxinivorans (14.2%) and Trichosporon faecale (4.7%). On IGS1 region sequencing the most predominant T. asahii type in our region was genotype 1 (16/17 isolates; 94.1%) and one isolate belonged to genotype 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…A noteworthy finding of our study is that only a limited number of Trichosporon isolates (10.5% [14/133 isolates]) were isolated from patients with hematological malignances, which were earlier reported to be one of the major underlying conditions (4, 5). Dabas et al also found that the incidence rate for Trichosporon bloodstream infections was lower in patients with malignancies than in those with gastrointestinal manifestations (22). In a study conducted by the Invasive Fungal Infection Group and the National Institute of Allergy and Infectious Diseases Mycoses Study Group in cancer patients (5,23), involving 30 centers and lasting 2 years, 269 cases of fungemia were reported but only 3 were caused by Trichosporon spp.…”
Section: Discussionmentioning
confidence: 99%
“…A noteworthy finding of our study is that only a limited number of Trichosporon isolates (10.5% [14/133 isolates]) were isolated from patients with hematological malignances, which were earlier reported to be one of the major underlying conditions (4, 5). Dabas et al also found that the incidence rate for Trichosporon bloodstream infections was lower in patients with malignancies than in those with gastrointestinal manifestations (22). In a study conducted by the Invasive Fungal Infection Group and the National Institute of Allergy and Infectious Diseases Mycoses Study Group in cancer patients (5,23), involving 30 centers and lasting 2 years, 269 cases of fungemia were reported but only 3 were caused by Trichosporon spp.…”
Section: Discussionmentioning
confidence: 99%
“…mycotoxinivorans (formerly Trichosporon mycotoxinivorans) is now considered a relevant pathogen for patients with cystic fibrosis (16). Moreover, this microorganism has been related to deep-seated infections in immunocompromised patients with invasive disposals in India (17). The use of Bruker's MALDI-TOF MS as a reliable tool for A. mycotoxinivorans species identification has helped strengthen the epidemiologic link of T. mycotoxinivorans to cystic fibrosis (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…A growing population of immunocompromised patients has resulted in frequent diagnoses of invasive fungal infections (IFIs), including those caused by unusual yeasts ( Dabas et al, 2017 ). Invasive candidiasis is a growing concern worldwide with high morbidity and mortality; it affects patients of all ages, including patients with malignancies, HIV-negative immunocompromised (IC) patients, and non-immunocompromised (NIC) patients among those who are critically ill, often admitted to an intensive care unit (ICU), or diagnosed with diabetes mellitus or uncontrolled hyperglycemia requiring invasive mechanical ventilation ( Berdal et al, 2014 ; Bitar et al, 2014 ; Epelbaum and Chasan, 2017 ; Alves et al, 2018 ; Ding et al, 2018 ; Mantadakis et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%